Perception of Emotion in Conversational Speech by Younger and Older Listeners - Schmidt, Juliane; Janse, Esther; Scharenborg, Odette (Frontiers in Psychology, 2016)
This study investigated whether age and/or differences in hearing sensitivity influence the perception of the emotion dimensions arousal (calm vs. aroused) and valence (positive vs. negative attitude) in conversational speech. To that end, this study specifically focused on the relationship between participants’ ratings of short affective utterances and the utterances’ acoustic parameters (pitch, intensity, and articulation rate) known to be associated with the emotion dimensions arousal and valence. Stimuli consisted of short utterances taken from a corpus of conversational speech. In two rating tasks, younger and older adults either rated arousal or valence using a 5-point scale. Mean intensity was found to be the main cue participants used in the arousal task (i.e., higher mean intensity cueing higher levels of arousal) while mean F0 was the main cue in the valence task (i.e., higher mean F0 being interpreted as more negative). Even though there were no overall age group differences in arousal or valence ratings, compared to younger adults, older adults responded less strongly to mean intensity differences cueing arousal and responded more strongly to differences in mean F0 cueing valence. Individual hearing sensitivity among the older adults did not modify the use of mean intensity as an arousal cue. However, individual hearing sensitivity generally affected valence ratings and modified the use of mean F0. We conclude that age differences in the interpretation of mean F0 as a cue for valence are likely due to age-related hearing loss, whereas age differences in rating arousal do not seem to be driven by hearing sensitivity differences between age groups (as measured by pure-tone audiometry).